Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Arshad, Muhammad Sohail; Hassan, Sana; Hussain, Amjad; Abbas, Nasir; Küçük, İsrafil; Nazari, Kazem (Springer International Publishing Ag, 2019)
Purpose The aim of this study was to design and characterize microneedle patch formulation containing cetirizine hydrochloride. Methods Chitosan was co-formulated with cetirizine hydrochloride. Transdermal patches were prepared by casting this solution to microneedle molds. Control patches were formulated by casting this solution to a plain cuvet of same area as mold but lacking microneedles. An array of methods namely; differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and scanning electron microscopy (SEM) were employed for the characterization of the films and the microneedles accordingly whereas in vitro permeation studies were conducted across rat skin. Light microscopy was performed to assess any histological changes upon microneedles application onto the rat skin. Results The patches had a reproducible thickness (0.86 +/- 0.06 mm) and folding endurance. Both the blank and drug loaded patches had 100 microneedles each of 300 micrometre length. In addition, the microneedle patches were ascribed with a two-fold increase in drug permeation across rat skin in the presence of microneedles as compared to the control formulations. Histological examination confirms a minimal invasion of the skin conferred by the microneedles. Conclusion The microneedle patches serve as an alternate route of drug administration in patients with nausea and swelling difficulties. Graphical abstract Microneedle patch manifest a two-fold increase in the skin permeation of Cetirizine Hydrochloride as compared to the control that is drug loaded patch without microneedles
Keywords: Microneedles; Transdermal Drug delivery; Cetirizine Hydrochloride